PENGARUH LINGKUNGAN TEMPAT TINGGAL TERHADAP AKSES LAYANAN KESEHATAN IBU DAN ANAK DI KOTA MEDAN - GIRSANG, ELIZABETH SEPTIANUR (LP2MTBM MAKARIOZ, 2022)
Medan is a city in the Sumatra region, where the number of children in Medan City is 776,345 people, while the number of mothers in Medan City is 530,988 people, where more than 50% of the population in Medan City is affected by infectious diseases due to environmental conditions. densely populated residential areas, poor sanitation levels, worrying air and water pollution conditions, poor air circulation conditions and inadequate air ventilation availability cause the health of the community, especially mothers and children, to be disturbed, which will result in medical staff are not providing the service properly, fearing that there will be a high transmission of the disease, thus making access to health services less than optimal, even disrupted which makes the services provided inadequate, thus causing the maternal and child mortality rate to increase by 40-50 %. This research aims to understand and analyze the influence of the environmental conditions where residents in Medan City live on access to maternal and child health services which is less than optimal. The method used in this research is the analytical descriptive method. The population in this study is that the number of children in Medan City is 776,345 people, while the number of mothers in Medan City is 530,988 people, while the sample size is 88 respondents consisting of of 44 mothers and children in the city of Medan who were affected by disease due to poor environmental conditions. The data collection techniques were carried out through observation and documentation studies. The results of the research show that the population with the most illnesses due to poor environmental conditions are mothers aged 25-29 years and children aged 10-14 years, while the number of mothers and children who tend to have bad illnesses due to inadequate sanitation conditions, thereby increasing the number of viruses or diseases that can be transmitted from sanitation that is not clean and good, which will cause disease conditions to worsen, thereby disrupting the health and activities of the population in a society so that they do not have appropriate ways to deal with them. deteriorating quality of the condition of facilities in the house and around it.